Seroprevalence of antibodies against leptospira spp in mares from a stud in Lima - Sotomayor R., Carlos (2012)
The seroprevalence of Leptospira spp in mares with abortion problems in a stud in Lima was determined. Two blood samples were collected from each mare within a 2-month period for the detection of antibodies against 12 Leptospira serovars using the microaglutination test. The serovars included in the study were icterohaemorraghiae, canicola, pomona, bratislava, georgia, tarassovi, autumnalis, pyrogenes, hardjo, ballum, australis and gryppotyphosa. Total prevalence of Leptospira spp was 96 and 100% in the first and second sampling respectively. Antibodies against serovars canicola, icterohaemorraghiae, pomona and georgia were more frequently detected during both period of sampling. No antibodies were found against serovars bratislava, tarassovi, autumnalis, hardjo, australis or gryppotyphosa. Sixty five percent of the animals were positive for three serovars simultaneously. The most frequent serovar was georgia (100%), which has not been reported as a pathogen for horses. The study showed the wide distribution of various Leptospira serovars in horses.